Analysis of Prospective Teachers' Self-Training Needs Regarding Mathematical Software Adaptation - Supriyo Supriyo; Ani Afifah; Rani Darmayanti; Syed Muhammad Yousaf Farooq (JTAM (Jurnal Teori dan Aplikasi Matematika), 2026)
In the modern educational landscape, the integration of technology into mathematics education is crucial, and prospective teachers are expected to be not only passive users but also adaptive developers of digital content. Despite being labeled as the "digital generation," a paradox has emerged where general technological proficiency does not equate to competence in specialized mathematics software. This study addresses the self-paced training needs of prospective mathematics teachers at Universitas PGRI Wiranegara, aiming to improve their ability to adapt learning software effectively. Using a qualitative descriptive approach, data were collected through questionnaires and in-depth interviews with final-year students, with the instruments validated through expert assessment and data triangulation to ensure reliability and accuracy. The study revealed a significant gap in technological proficiency: 88% of respondent demonstrated proficiency in basic visualization techniques, but only 4% mastered advanced features such as scripting. Analysis of self-paced learning patterns highlighted issues such as fragmented learning, reactive learning, and high cognitive load, underscoring the urgent need for a structured, project-based self-paced training roadmap. This roadmap will guide prospective teachers from understanding mathematical abstractions to effectively implementing digital functions, empowering them to become competent digital content developers and increasing the effectiveness of their teaching in technologically integrated classrooms.